Modern views on physical activity in the prevention of concomitant pathology in individuals after cholecystectomy as a prerequisite for the substantiation and development of a physical rehabilitation program - Nataliya Golod (Kazimierz Wielki University, 2017)
Actuality. The absence of physical activity (PA) harms the health and normal functional capacity of organs and is the main cause of most chronic diseases, including in patients with gallbladder disease (GBD) and after cholecystectomy (CC). Objectives of research. To analyze the causes and risk factors for the development of GBD. To analyze the effect of PA on the human body. To determine the directions of physical rehabilitation to improve the quality of life of people after cholecystectomy with concomitant pathology. Results of research. The risk factors for the development of GBD are low FA, overweight, obesity, smoking, female sex, childbirth before the age of 20, postmenopausal medication, diet (consumption of large amounts of calories from refined carbohydrates, animal protein and cholesterol and low content of vegetables and dietary fiber). CC is a trigger for the development of metabolic dysfunctions. FA deficiency and metabolic dysfunctions after CC lead to further development of comorbidities - a combination of factors, namely endothelial dysfunction in the form of insulin resistance, abdominal obesity, hypertension, dyslipidemia, is defined as metabolic syndrome (MS). Conclusions. Increasing FA and exercise training (ET) is an effective therapeutic strategy to improve endothelial function and, as a result, reduce the symptoms of cardiovascular disease (CVD), normalize lipid profile, slow the progression of diabetes mellitus (DM) and its consequences, reduce body mass index (BMI), blood pressure (BP), and the risk of stroke. The use of ET in people after CC with comorbidities should be individualized, taking into account age, gender, recovery period, lifestyle, and existing concomitant pathology. For effective positive changes, physical rehabilitation programs should last at least 12 weeks.  The intensity and number of ET sessions for people after CC requires more thorough further study.